1999
DOI: 10.1002/(sici)1098-2736(199903)36:3<333::aid-tea7>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between secondary science teachers' orientation to traditional culture and beliefs concerning science instructional ideology

Abstract: This study sought to measure secondary science teachers' level of commitment to traditional culture in Zimbabwe and how this orientation is related to their beliefs concerning science instructional ideology. The study involved 63 in-service science teachers studying for the bachelor of education degree at the University of Zimbabwe. The science teachers in this study maintain a fairly traditional posture with regard to aspects of traditional authority, religion, view of nature, and social change. They show a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…This input resonates with the literature on science education. Overson Shumba (1999), for example, in talking about traditional and cultural beliefs of science teachers in Zimbabwe, says that:…”
Section: Bhutan's Education Systemmentioning
confidence: 89%
“…This input resonates with the literature on science education. Overson Shumba (1999), for example, in talking about traditional and cultural beliefs of science teachers in Zimbabwe, says that:…”
Section: Bhutan's Education Systemmentioning
confidence: 89%
“…We are reminded, where science intersects with beliefs, that "worldview is the overall perspective from which one sees and interprets the world" (Shuumba, 1999;p. 333).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to the above, teacher authority in Bruneian non-government secondary schools [30] has been reported to be comparable to in Australian schools [5]. Research has also shown that respondents' perceptions are influenced by demographic variables [4,5,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these emphases are similar to those found in some developing and developed countries [32]. However, at the lower-secondary level, Bruneian society does not approve of the free mixing of genders and therefore male and female students sit in different rows, which affects the classroom learning environment.…”
Section: Introductionmentioning
confidence: 99%